A CROSS-SECTIONAL OBSERVATIONAL STUDY ON KNOWLEDGE, ATTITUDE, AND PRACTICE REGARDING HANDLING OF EXPIRED MEDICINES AMONG DOCTORS IN A TERTIARY CARE HOSPITAL - JAYASREE D; SOWMYA DEEPTHI CHAVALA; DARA ARUNA KUMARI; NAGA JYOTHI V (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The present study was conducted to assess knowledge, attitude, and practice related to use and disposal of expired medicines among doctors working in a tertiary care hospital. Methods: The study was conducted in the Government Medical College, Nandyal, Andhra Pradesh. After obtaining verbal consent, a pre-validated questionnaire was shared to the participants through Google Forms. It had two parts; part one with participant demographic details and part two comprised structured multiple choice questions, regarding their knowledge, attitude, and practice toward handling of expired medicines. Forms with completed responses were included and analyzed using Microsoft Excel 2007. Results: A total of 84 responses were analyzed, and it was observed that 88% of the participants knew the definition of expiry date and its calculation. All the participants checked for the expiry date always. About 66% opined that expired drugs should never be used. Only 37% were aware of the color-coded bin used to dispose expired medication. About 33% responded that pharmaceutical waste can be reduced by rational drug use. Conclusion: The study shows that there is lacuna regarding knowledge, attitude, and practice related to use of expired drugs and their disposal. It is recommended to create awareness regarding the same though workshops and awareness programs.